5x(7xy + 6x + 8)
2(5x - 1)(3x - 2)
(10x - 3)(3x + 10) so x = 3/10 or -10/3
This is an expression and you do not solve an expression, but you can factor this one.X2 + 3X4X2(1 + 3X2)========
x=1/3,3/5
5x squared plus 33x plus 18 = (5x + 3)(x + 6) x = -6, -3/5
If you can't factor it easily, use the quadratic formula.
If you can't factor it easily, use the quadratic formula.
(x - 1)(x^2 - 5x + 2)
Convert feet and inches to inches plus inches. Then use the cm per inch conversion factor.
x2 - 8x + 32 = 0 (assuming)you can factor or use the quadratic equation.I recommend the quadratic equation.
-- Factor the left side of the equation. -- Set one factor equal to zero, and solve it for 'x'. That gives you one solution to the equation. -- Set the other factor to zero, and solve it for 'x'. That gives you the other solution to the equation. -- If you don't get x=2 and x=-8/3 then repeat the previous steps, because you made a mistake the first time.